Social evolution and diminished olfactory function in larval honey bees - Tianfei Peng; Zhenqing Chen; Amy C. Cash Ahmed; Qianlu Feng; Seokjin Yeo; Hee-Sun Han; Gene E. Robinson (Proceedings of the National Academy of Sciences, 2026)
Social evolution made larval honey bees dependent on adult colony members for feeding; they are confined to cells in waxen honeycombs and visited about 100 times per day by adult “nurse” bees. Based on organismal resource conservation theory, we predicted larvae have diminished olfactory capabilities at both the molecular and behavioral levels. Consistent with theory, larvae expressed very low levels of Orco , an essential gene for olfactory receptor (OR) function. By contrast, they showed higher expression of Ir25a, essential for other forms of sensory perception including gustation. Also consistent with theory, behavioral assays demonstrated that larvae cannot find food via olfaction, suggesting they use taste for feeding. By contrast, it is known that adult honey bees use OR-based olfaction extensively for a variety of behavioral functions, and the honey bee genome contains many OR-encoding genes. Comparative transcriptomic analyses of social and nonsocial insects suggest that this developmentally regulated suppression of olfactory function is related to social evolution, especially systems of offspring care.